Cloning and sequence analysis of three novel chalone synthase genes in Cryptomeria plants - LU Yongquan; JIA Qing; TONG Zaikang; CHEN Jianyang (浙江大学学报. 农业与生命科学版)
Chalcone synthase（CHS）is the first enzyme in the flavonoid biosynthetic pathway in plants. In order to clone CHS gene in Cryptomeria plants, the amplified consensus genetic markers（ACGM）were designed and combined with RACE technique, three CHS genes in Cryptomeria japonica var. sinensis, C. japonica cv. Araucarioides and C. japonica were obtained, respectively. Sequence analysis showed that the coding sequence（CDS）of each CHS gene was 1 176 bp in length and encoded 391 amino acids. The GFGPG tag of CHS conservative active sites were found in their proteins. Three CHS proteins showed 99% homology with each other, but more than 79% homology with other plants, which indicated that CHS were relatively conserved during evolution.